Evaluation of the Implementation Policy of Menpan RB Regulation No. 3 of 2023 on the Bureaucratic Reform Index in the Indonesian National Army (TNI) - Rosadi, Hengky; Ferdiansyah, Muhammad Luthfi; Ridho, Sari Lestari Zainal; Fadila, Dewi; Mohamad Ali, Habsah Binti Haji (Pelopor Publikasi Akademika, 2025)
Corporate social responsibility is mandatory for companies in Indonesia. It is primarily implemented in the company's Ring 1 area, namely in areas where communities are most disturbed by the presence and activities of corporations and are directly involved with corporate activities. One of the implementations of corporate social responsibility at PT Pertamina EP Prabumulih Field is through the Empowered Women, Managing Waste Together (MUDA BERSAMA) Program. This research took the form of qualitative field research to examine the program. The research results show that the Empowered Women, Managing Waste Together (MUDA BERSAMA) Program is a community development activity in the field of environmentally friendly, healthy and sustainable agriculture in Patih Galung Village, West Prabumulih District, Prabumulih City. The main actor running this program is the Kemuning Women Farmers Group (KWT). Some of its activities include planting organic vegetables and Family Medicinal Plants (TOGA), making processed products, making compost, Liquid Organic Fertilizer (POC) and Local Microorganisms (MOL). There is also the Matoa Women Farmers Group (KWT) which focuses on managing organic waste in their area. The MUDA BERSAMA program has directly benefited 30 members and indirectly benefited 657 residents of Patih Galung Village. The program has four impact categories, which also represent concrete examples of the Village SDGs launched in Indonesia: nature, economy, well-being, and society.